Retrospective of Human Rights Activities of the World Federation of Ukrainian Women’s Organizations - I. V. Periv (Науковий вісник Ужгородського національного університету. Серія Право)
The article provides a retrospective analysis of the human rights activities of the World Federation of Ukrainian Organizations (WFUO), which unites Ukrainian diaspora structures in the struggle for the rights of Ukrainians in the world. The main directions of the Federation’s work are disclosed, in particular the protection of human rights, support of political and public initiatives aimed at preserving national identity, the fight against repression and discrimination. Emphasis is placed on the main areas of activity of the World Federation of Ukrainian Women’s Organizations (WFUHO), which are aimed at protecting the rights and freedoms of Ukrainian women, strengthening their social status and participation in public and political life. Special attention is paid to the struggle for the rights of women who have suffered from gender discrimination, violence or repression, particularly in the context of military conflicts, migration and other crisis situations. One of the important areas of work of SFUZHO is the preservation of national identity among the Ukrainian diaspora. The organization contributes to the development of Ukrainian culture, language, traditions and the education of future generations in the spirit of respect for the national heritage. This activity includes supporting Ukrainian schools abroad, holding cultural events, publishing literature in the Ukrainian language, and organizing international forums. In addition, SFUZHO actively draws the attention of the world community to human rights violations in Ukraine. The organization acts as an initiator and participant of international conferences, protest actions, publications in international media and advocacy campaigns in leading world institutions. Their activities gained special importance during periods of political crises in Ukraine, such as the Revolution of Dignity and Russia’s military aggression. Thus, SFUZHO plays an important role both in the struggle for the rights of Ukrainian women and in maintaining national identity and raising the awareness of the world community about human rights issues in Ukraine.